Freund’s adjuvant is a classic of vaccine adjuvants and the basis of experimental immunology - F.V. Hladkykh (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. The invention of vaccines is rightfully considered one of the triumphs of medical research and one of the most remarkable achievements in public health in the history of humanity. According to the World Health Organization, vaccination saves 5 lives every minute and has saved over 25 million lives from 2011 to 2020. The effectiveness of a vaccine depends not only on the components of the antigen but also on the adjuvants, which are often used for more effective stimulation of the immune system.